(untitled) (American Journal of Pedagogical and Educational Research, 2022)
The article deals with the issues based on specifics of organizing the process of preparing future sports coaches to overcome conflicts between team members on the basis of an acmeological approach, and describes specific aspects of conflict resolution in the pedagogical process.